Plant cell biology - Anderson, Charles T.; Haswell, Elizabeth; Dixit, Ram (Methods in cell biology, 2020)
Intro -- Plant Cell Biology -- Copyright -- Contents -- Contributors -- Part I: Membrane and cytoplasm -- Chapter 1: Perturbation and imaging of exocytosis in plant cells -- 1. Introduction -- 2. Materials, reagents and equipment -- 2.1. Materials and reagents -- 2.2. Equipment -- 3. Perturbing plant exocytosis using ES2 -- 3.1. Plant sample preparation -- 3.2. ES2 treatment -- 3.3. Image quantification -- 4. Using Brefeldin A to perturb protein trafficking -- 4.1. BFA treatment -- 4.2. BFA washout -- 4.3. Quantification of BFA compartment abundance -- 5. Analyzing CSC exocytosis dynamics using FRAP -- 5.1. Sample preparation and mounting -- 5.2. Image collection and image processing to quantify CSC delivery events -- Acknowledgment -- References -- Chapter 2: Electron tomography and immunogold labeling of plant cells -- 1. Introduction -- 2. Sample preparation -- 2.1. Overview -- 2.2. Materials and reagents -- 2.3. High-pressure freezing -- 2.4. Freeze substitution -- 2.4.1. Freeze substitution for structural analysis using dry ice -- 2.4.2. Freeze substitution for immunogold labeling using a freeze-substitution device -- 2.5. Sectioning, staining, and application of gold fiducials for electron tomography -- 3. Image acquisition and analysis -- 3.1. Overview -- 3.2. Image acquisition -- 3.3. Calculation of electron tomograms -- 3.4. Segmentation and analysis -- 4. Immunolabeling -- 4.1. Overview -- 4.2. Materials and reagents -- 4.3. Immunolabeling -- 5. Conclusions -- Acknowledgment -- References -- Chapter 3: Methods for studying protein targeting to and within the chloroplast -- 1. Rationale -- 2. Synthesis of in vitro translated and radiolabeled substrate -- 2.1. Rationale -- 2.2. Materials -- 2.3. Protocol -- 2.4. Analysis -- 2.5. Alternative methods and optimization -- 3. Synthesis of recombinant substrate in E. coli -- 3.1. Rationale.